Efeitos de espaçamentos entre e dentro das fileiras de plantio sobre duas variedades de soja, em Viçosa e Capinóp - Sediyama, Tuneo; Américo Cardoso, Antônio; Vieira, Clibas; Athow, Kirk L (Revista Ceres, 2025)
In 1969/70 the effect ofspacing between rows and the distance between plants within the row on height of first pod, plant height, lodging, yield, seed size, and seed quality was studied to determinate soybean variety "Viçoja" at Viçosa and Capinópolis and the indeterminate soybean variety "LAC-2" at Viçosa.